Effects of bio fertilizer and nano Zn-Fe oxide on physiological traits, antioxidant enzymes activity and yield of wheat (Triticum aestivum L.) under salinity stress - Khadijeh Babaei; Raouf Seyed Sharifi; Alireza Pirzad; Razieh Khalilzadeh (Journal of Plant Interactions, 2017)
In order to evaluate the effects of nano Zn-Fe oxide and bio fertilizer on physiological traits, antioxidant activity and yield of wheat under salinity stress, a factorial experiment was conducted based on RCBD with three replications.Treatments were included salinity in three levels (no-salt, salinity 25 and 50 mM NaCl), four bio fertilizers levels (no bio fertilizer, seed inoculation by Azotobacter, Azosperilium, Pseudomonas) and nano oxide (without nano, application of nano Zn oxide, nano Fe oxide and nano Fe-Zn oxide 1.5 g/lit). Salinty stress decreased the chlorophyll-a, chlorophyll-b, total chlorophyll, photochemical efficiency of PSII and yield of wheat, whearas electrical conductivity, soluble sugars, proline content, and the activities of Catalase (CAT), Peroxidase (POD) and Polyphenol Oxidase (PPO) enzymes increased. Similar results were observed in CAT, POD and PPO activities due to inoculation by bio fertilizers and nano oxide. Maximum of soluble sugars and proline content were observed in the highest salinity level and application of Pseudomonas. Application of nano Zn-Fe oxide increased about 17.40% from grain yield in comparision with no application of nano oxide in the highest salinity level. Generally, it was conducted that bio fertilizer and nano oxide can be used as a proper tool for increasing wheat yield under salinity condition.